"First meetings": constructive first encounters between pre-service teachers and their mentors. Issue 4 (30th July 2020) - Connolly, Steve; Bates, Gareth; Shea, James
Abstract : Purpose: The purpose of this paper is to report the findings from an action research project in which the researchers sought to develop a set of questions for use by mentors (experienced teachers) and mentees (pre-service teachers) on a course of initial teacher education (ITE) when they first met – the "initial encounter". Design/methodology/approach: The researchers used an action research approach in order to address the lower retention rate of pre-service teachers from different backgrounds, such as Black and Minority ethnic (BAME) and the issues around mentoring which may exacerbate this problem. Discussions between the course team and participating mentors and mentees suggested that the initial encounter between mentor and mentee was significant, and an action research methodology would allow for developing questions that might structure such encounters. Findings: The researchers found that a useful and effective set of questions could be developed and used by mentors and mentees. Additionally, this process gave researchers insights into the nature of the first encounters between mentors and mentees on an ITE course and how both groups see their roles. In several cycles of action research, the participants produced a number of iterations of such questions, which were refined across a two-year period. Research limitations/implications: While it is too early to tell if the issues leading to the lower retention rate of pre-service teachers that prompted the project have been reduced in any significant way, the researchers suggest that thinking about these initial encounters can have an impact on the way mentors and mentees go on to build a relationship. Originality/value: The authors found that there is very little research in the field of teacher education which looks at initial encounters between mentors and mentees, and thus make an original contribution to the mentoring literature.